1995
DOI: 10.1016/0168-6445(95)00023-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of the electron transfer system which participates in the oxidation of ferrous ion by Thiobacillus ferrooxidans

Abstract: The enzymes and redox proteins, which participate in the oxidation of ferrous ion by the acidophilic iron-oxiding bacterium Thiobacillus ferrooxidans, have been isolated and characterized. They are Fe(II)-cytochrome c oxidoreductase, cytochromes c-552(s), c-552(m) and c-550(m), rusticyanin, and cytochrome c oxidase. On the basis of the interactions of these components, an electron transfer system has been proposed which seems to function in the oxidation of ferrous ion by the bacterium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 34 publications
1
52
0
Order By: Relevance
“…Among the cytochromes C~~~( S ) (13 kDa), cSS2(m) (21 kDa), and csso(m) (68 kDa) described by Yamanaka [17], only ~~~~( s ) , which is not auto-oxizable, in contrast to cytochrome c, , seems to be involved in the respiratory chain. Cytochrome c,,,(s) is reduced by Fe(I1) : cytochrome c-oxidoreductase in the presence of Fez+ at pH 3.5 and is oxidised by cytochrome oxidase.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Among the cytochromes C~~~( S ) (13 kDa), cSS2(m) (21 kDa), and csso(m) (68 kDa) described by Yamanaka [17], only ~~~~( s ) , which is not auto-oxizable, in contrast to cytochrome c, , seems to be involved in the respiratory chain. Cytochrome c,,,(s) is reduced by Fe(I1) : cytochrome c-oxidoreductase in the presence of Fez+ at pH 3.5 and is oxidised by cytochrome oxidase.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, upon aligning the two cytochromes isolated from two different strains of 7: ferrooxidans, they were found to have a large degree of identity (64%). The two cytochromes c552 (soluble and membrane bound) isolated by Yamanaka [17] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact role of each of these carriers in the electron transport pathway of Fe(II) oxidation, however, is uncertain and controversial. In particular, there is debate on where Fe(II) oxidation takes place in the cell (2,5,58), although there is general agreement that the Fe(II) oxidase is located external to the cytoplasmic membrane.…”
mentioning
confidence: 99%
“…Although the same amounts of ferrous iron were oxidized when strains MON-1 and ATCC 23270 gave maximum cell yields, the growth yield of strain MON-1 was It is well known that aa 3 type cytochrome c oxidase is one of the most important components of the iron oxidation enzyme system in A. ferrooxidans. 32,[35][36][37][38][39][40][41][42][43][44] We have found that mercury resistant-A. ferrooxidans strains SUG 2-2 and MON-1 have high Fe 2þ -dependent mercury volatilization activity in the cells, 30,31) and that cytochrome c oxidase purified from strain SUG 2-2 reduces Hg 2þ with Fe 2þ as electron donor volatilizing metalic mercury (Hg 0 ) outside of the cells.…”
Section: Growth Of a Ferrooxidans Strains In An Iron Medium Supplemementioning
confidence: 99%